2007
DOI: 10.1177/03946320070200s203
|View full text |Cite
|
Sign up to set email alerts
|

Acute Impact of Volcanic Ash on Asthma Symptoms and Treatment

Abstract: Information about the impacts of disasters on health is useful for establishing hazard prediction maps and action plans of disaster management. This study aims at learning effective asthma management from the volcano disaster of Mount Asama eruption in Japan on September 1, 2004. We conducted a cross-sectional study to assess the acute impact of volcanic ash on asthma symptoms and their treatment changes by using a questionnaire completed by 236 adult asthmatic patients and their physicians. In the ashfall ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
1
5
1
1
Order By: Relevance
“…A Japanese study of asthma treatment and volcanic ash exposure found worsening of symptoms in asthmatics in areas with more than 100 g/m 2 ash, but not in areas with less ash fall 34. The psychological morbidity found in the current study (20–26%) was lower than that found in the survey of the most exposed area right after the Eyjafjallajökull eruption ended (39%) 7.…”
Section: Discussioncontrasting
confidence: 79%
“…A Japanese study of asthma treatment and volcanic ash exposure found worsening of symptoms in asthmatics in areas with more than 100 g/m 2 ash, but not in areas with less ash fall 34. The psychological morbidity found in the current study (20–26%) was lower than that found in the survey of the most exposed area right after the Eyjafjallajökull eruption ended (39%) 7.…”
Section: Discussioncontrasting
confidence: 79%
“…The children had normal spirometry measurements. Previous studies have not found changes in lung function in children after volcanic ash exposure, but asthma hospitalisation rates have been seen to increase after several eruptions,11 12 and a dose–response has also been found in a Japanese study of asthmatic adults who were exposed to volcanic ash 28…”
Section: Discussionmentioning
confidence: 90%
“…A study of individuals with symptomatic asthma and acute bronchitis, and healthy controls, from communities heavily impacted by the eruption, supported the a priori hypothesis that preexisting respiratory diseases are important risk factors for adverse respiratory reactions to volcanic ash (Bernstein et al, 1986). Similarly, after the 2004 eruption of Mount Asama in Japan, a survey of 236 asthmatic adults found 43% experienced exacerbations, compared to 8% in an unexposed control area; those cases with more severe asthma did not experience such changes, as these individuals apparently tended to reduce their exposure by staying indoors with closed windows (Shimizu et al, 2007).…”
Section: Health Effects From Exposure To Volcanic Ashmentioning
confidence: 68%